Software business : 9th International Conference, ICSOB 2018, Tallinn, Estonia, June 11-12, 2018, Proceedings /: 9th International Conference, ICSOB 2018, Tallinn, Estonia, June 11-12, 2018, Proceedings. (2018) - Unknown
No abstract available